2000
DOI: 10.1038/sj.cdd.4400639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the bifunctional redox factor / AP endonuclease Ref-1 is an anti-apoptotic protein associated with differentiation in the developing retina

Abstract: Retinal cell differentiation leads to resistance to apoptosis induced by inhibition of protein synthesis, suggesting the accumulation of anti-apoptotic proteins. The redox factor/AP endonuclease Ref-1 (APE, APEX, HAP1) affects both DNA repair and the activity of various transcription factors, and controls sensitivity to genotoxic insults. We studied the expression of Ref

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Moreover, overexpressing Ape1/Ref-1 in hippocampal and sensory cells results in a significant increase in cell viability after exposure to hydrogen peroxide (89). Preventing the loss of Ape1/Ref-1 by inhibiting protein synthesis rescued neurons from experimentally induced cell death (13). We have shown here that Ape1/Ref-1 expression led to enhancement of neuronal differentiation and survival (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, overexpressing Ape1/Ref-1 in hippocampal and sensory cells results in a significant increase in cell viability after exposure to hydrogen peroxide (89). Preventing the loss of Ape1/Ref-1 by inhibiting protein synthesis rescued neurons from experimentally induced cell death (13). We have shown here that Ape1/Ref-1 expression led to enhancement of neuronal differentiation and survival (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Previous work from our laboratory showed that thapsigargin selectively kills photoreceptors in the outer nuclear layer of retinal explants from 1-week-old rats (33). The degeneration of rhodopsin-containing photoreceptors was also prevented by PACAP38 (Fig.…”
Section: Pacap38 Is a Potent Neuroprotective Agent In The Newbornmentioning
confidence: 59%
“…Counts of pyknotic profiles were made at ϫ1000 magnification under oil immersion in three random fields of 0.0148 mm 2 within the neuroblastic layer, and at least three randomly selected explants were analyzed for each group in each experiment. Photoreceptor cell death was identified by the round and condensed morphology of rhodopsin-positive profiles within the outer nuclear layer, wherein normal photoreceptors present an elongated shape at that age (33). Counts were made at ϫ1000 magnification under oil immersion in three random fields of 0.0074 mm 2 within the outer nuclear layer.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these two activities seem to be fundamental in the works (14,96,126). APEl/Ref-1 expression is always inversely correlated with the onset of apoptosis, suggesting a role as an antiapoptotic molecule.…”
Section: General Considerations Onapel/ref-1 Biological and Molecularmentioning
confidence: 99%